Pengaruh Disrupsi Digital Menggunakan Content Marketing Terhadap Keputusan Pembelian Produk pada Umkm di Kota Denpasar - Ni Made Widnyani; Ni Luh Putu Surya Astitiani (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
The purpose of making this article is to find out how digital disruption using content marketing influences the purchasing decisions of MSME products in Denpasar City. There are several things that can influence the decision to purchase a product, but there are factors that are rarely measured, namely digital disruption using content marketing. This article includes a quantitative study with the obtained from the questionnaire. The samples used were 99 samples. Data analysis in this study used the SmartPLS program. The research results show that digital disruption has a significant positive effect on the creation of MSME content marketing in Denpasar City. Digital disruption also has a significant positive influence on product purchasing decisions for SMEs in Denpasar City, and in mediation, content marketing has a significant positive influence on purchasing decisions for SMEs products in Denpasar City.